Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2012
DOI: 10.1145/2207676.2208709
|View full text |Cite
|
Sign up to set email alerts
|

Look & touch

Abstract: While eye tracking has a high potential for fast selection tasks, it is often regarded as error-prone and unnatural, especially for gaze-only interaction. To improve on that, we propose gaze-supported interaction as a more natural and effective way combining a user's gaze with touch input from a handheld device. In particular, we contribute a set of novel and practical gaze-supported selection techniques for distant displays. Designed according to the principle gaze suggests, touch confirms they include an enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(23 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Where gaze shifts involve head movement, it is the eyes that reach a target first while the head follows more slowly [4]. However, eye movement is jittery and a variety of techniques employ gaze for coarse-grained positioning in combination with mouse, pen or touch for refinement [40,51,53,60]. While conventional pointing uses a cursor metaphor, it is less clear how best to provide feedback with gaze as eye movement is primarily engaged in information seeking rather than target identification [17].…”
Section: Gaze-based Pointing and Selectionmentioning
confidence: 99%
“…Where gaze shifts involve head movement, it is the eyes that reach a target first while the head follows more slowly [4]. However, eye movement is jittery and a variety of techniques employ gaze for coarse-grained positioning in combination with mouse, pen or touch for refinement [40,51,53,60]. While conventional pointing uses a cursor metaphor, it is less clear how best to provide feedback with gaze as eye movement is primarily engaged in information seeking rather than target identification [17].…”
Section: Gaze-based Pointing and Selectionmentioning
confidence: 99%
“…Additional modalities, e. g., touch, are used to circumvent these limitations. We call such interfaces gaze-supported [139]. Stellmach et al [140] presented a system for the gaze-supported exploration of large image databases.…”
Section: Gestural Interactionmentioning
confidence: 99%
“…Under normal conditions, the eye is used to gain information about the environment, but not to trigger commands. However, different studies have shown the gain in task performance if gaze is combined with other modalities, such as touch or head gestures [SD12,MHP12]. Recently, gaze-based interaction has been employed for Locked-In Syndrome (LIS) patients combining eye movement and electroencephalogram (EEG) signals confirming or cancelling gaze-based actions [HLZ * 16].…”
Section: Tracking Applicationsmentioning
confidence: 99%